Microbiology : an introduction - Tortora, Gerard J.; Funke, Berdell R.; Case, Christine L., 1948- (Harlow, United Kingdom : Pearson, 2021)
For pre-nursing and allied health students (including mixed-majors courses). Cutting edge microbiology research for today's learners Tortora, Funke, and Case's Microbiology, An Introduction brings a 21st-century lens to the #1 best-selling text on the market. Known for its excepti.
Previous edition: published as by Gerard J. Tortora, Berdell R. Funke, Christine L. Case. Boston: Pearson, 2016.
"Authorized adaptation from the United States edition, entitled 'Microbiology: an introduction,' 13th edition"--Title page verso.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Microbiology; Microbiology; Microbiologie